Exploring CGIAR’s efforts towards achieving the Paris agreement’s climate-change targets - Ngaiwi, Mary Eyeniyeh; del Mar Esponda, Maria; Amahnui, George Amenchwi; Villarino, Ma Eliza; Andrade, Robert; Castro-Nunez, Augusto (Elsevier, 2024)
This study delves into the evolutionary path of food and agricultural research and development organizations, aligning with the ambitious climate-change objectives outlined in the Paris Agreement. Our exploration revolves around advancing the triple goals of creating sustainable, low-emission food systems, enhancing nutrition, and ensuring food security. A pivotal consideration emerges from the recent United Nations Framework Convention on Climate Change's Conference of the Parties, where civil society advocacy gained momentum, emphasizing the need to seamlessly integrate food and nutrition security within climate-change mitigation initiatives. The objective of this study is therefore to examine how development organizations' agriculture and food research incorporates climate-change mitigation to address food security, health, and environmental sustainability challenges. In light of this, we undertook an examination of CGIAR's published articles, existing research initiatives, and a curated selection of innovations, with a focus on regional climate-change priorities. Our analysis not only underscores CGIAR's commitment to climate-change research, but also evaluates its contribution to reducing greenhouse gas emissions within food systems. Noteworthy is the discernible shift in CGIAR's research portfolio, reflecting a response to the escalating demand for environmental sustainability and an increased awareness of the interconnected nature of malnutrition and food security. While CGIAR has made significant strides in climate-change adaptation efforts, our analysis indicates an incomplete integration of food-systems perspectives for mitigating climate change. Our proposed approach advocates a comprehensive strategy that harmonizes adaptation and mitigation research, encourages cross-CGIAR collaboration through institutional changes, and underscores the importance of scaling innovations. This holistic endeavor highlights the type of research CGIAR is developing, seamlessly integrating the food-systems approach into the broader climate-change research agenda.